The Effects of Activator Treatment on the Lip Profile - Mete Özer; Selim Arıcı (Galenos Yayinevi, 2005)
The aim of this study was to investigate the changes of soft tissue profile in Class II division 1 cases, treated with activator and to compare the results with those of a control group. Records of 30 patients treated with activator were used in this study. Records of 15 patients who had class II division 1 malocclusion and had no treatment were also used as control. Soft tissue and skeletal landmarks were traced from lateral skull cephalometric radiographs taken before treatment and at the end of the active phase of the activator treatment (mean 11,8 month). For control groups the mean time between the first and second radiographs was 10,7 months. Paired t-test was used to compare the first and second measurements within the groups. Mann-Whitney U test was used to analyze the differences between the groups. There was a tendency for the nasolabial angle to decrease in the activator group, but this decrease was not statistically significant. Height of the upper lip was significantly increased in the activator group. The horizontal distance between E line and the most prominent anterior surface of the upper lip was increased in the activator group. In conclusion, two groups showed similar changes in the sagital and vertical dimensions of the soft tissues, however the means varied between the groups.